Descriptive Investigation of Government Events and Public Interest Analysis Using Google Trends between Pictorial Health Warnings Policy Implementation and Electronic Nicotine Delivery Systems Ban in India (Medico Legal Update, 2021)
Background: A sequential descriptive analysis of the government events related to 85% PW implementationand ENDS ban is lacking. There is also a dearth of public interest analysis in such policy making.Objectives: To descriptively analyse the sequence of government events in both the policies and evaluatethe public interest analysing trends from the respective events.Method: Government events in India on 85% PWs were collected from media articles ranging from October2014 to April 2016 while on ENDS ban, the information was obtained from Ministry of Health & FamilyWelfare, Government of India from August 2018 to December 2019. We compared Google Trends relativesearch volume data for ‘smoking causes cancer’, ‘smoking danger’, ‘pictorial’, ‘ITC limited’ as keywordsfor Pictorial Health Warnings from April 2014 to April 2016 (Policy A) while keywords such as ’electroniccigarettes, ’Vape’, ‘Juul’ were used as surrogate for ENDS ban from October 2017 to October 2019 (Policy B).Results: According to the Google trends analysis, ‘pictorial’ was searched significantly more in PolicyA time period (4298 vs 2599) while ‘Vape’ had distinctly more searches in Policy B time period (6136 vs1042). However, the volume of difference between the two policies time period was significantly higher forVape (5094 vs 1699).Conclusion: Strategy and experiences from delayed implementation of pictorial health warnings has laiddown the path for faster enactment of future anti-tobacco policies.